Rapid response of breast cancer to neoadjuvant intramammary testosterone-anastrozole therapy: neoadjuvant hormone therapy in breast cancer - Glaser, Rebecca L. (Lippincott-Raven Publishers, 2014)
OBJECTIVE: Experimental and clinical data support the inhibitory effect of testosterone on breast tissue and breast cancer. However, testosterone is aromatized to estradiol, which exerts the opposite effect. The aim of this study was to determine the effect of testosterone, combined with the aromatase inhibitor anastrozole, on a hormone receptor positive, infiltrating ductal carcinoma in the neoadjuvant setting. METHODS: To determine clinical response, we obtained serial ultrasonic measurements and mammograms before and after therapy. Three combination implants—each containing 60 mg of testosterone and 4 mg of anastrozole—were placed anterior, superior, and inferior to a 2.4-cm tumor in the left breast. Three additional testosterone-anastrozole implants were again placed peritumorally 48 days later. RESULTS: By day 46, there was a sevenfold reduction in tumor volume, as measured on ultrasound. By week 13, we documented a 12-fold reduction in tumor volume, demonstrating a rapid logarithmic response to intramammary testosterone-anastrozole implant therapy, equating to a daily response rate of 2.78% and a tumor half-life of 23 days. Therapeutic systemic levels of testosterone were achieved without elevation of estradiol, further demonstrating the efficacy of anastrozole combined with testosterone. CONCLUSIONS: This novel therapy, delivered in the neoadjuvant setting, has the potential to identify early responders and to evaluate the effectiveness of therapy in vivo. This may prove to be a new approach to both local and systemic therapies for breast cancer in subgroups of patients. In addition, it can be used to reduce tumor volume, allowing for less surgical intervention and better cosmetic oncoplastic results.